PERAN KANTOR IMIGRASI KELAS I KHUSUS TEMPAT PEMERIKSAAN IMIGRASI (TPI) SOEKARNO-HATTA DALAM RANGKA PENGAWASAN ORANG ASING DI INDONESIA: The Role of Exclusive Class I Immigration Office at Soekarno-Hatta International Airport Check Place (TPI) in the Framework of Foreign Citizen Control - Nurafifa, Ninda; Sulistyowati, Tri (AMICUS CURIAE, 2024)
Efforts to mitigate the disruptive effects of foreign visitors' admission and leave into Indonesia are governed by the country's immigration laws. Controlling the behavior of aliens is a part of the immigration process. In this piece, we discuss the challenges encountered by the Soekarno-Hatta Special Class I Immigration Office (TPI) and how they affect their ability to provide immigration supervision to foreign nationals seeking entry into Indonesia. Foreigners are strongly discouraged from entering Indonesia. This study is an example of the normative, descriptive research type. Qualitative in-depth interviews supplement secondary sources of information for this study. According to the findings, the TPI Soekarno-Hatta Special Class I Immigration Office is responsible for monitoring the activities of foreigners entering Indonesian territory through both administrative supervision (verifying immigration documents, conducting interviews, and checking the deterrence list) and field supervision (monitoring against the activities of foreigners). A lack of human resources, a lack of facilities and infrastructure at the TPI Soekarno-Hatta Special Class I Immigration Office, and an inadequate budget all work against the TPI Soekarno-Hatta Special Class I Immigration Office's ability to carry out immigration supervision of foreigners. visitors from outside Indonesia.